Spin orbit torque induced asymmetric depinning of chiral Néel domain wall in Co/Ni heterostructures - Ramu, Maddu (2017)
In this letter, we report on distinct depinning of a chiral Néel domain wall (DW) driven by spin-orbit torque (SOT) in Co/Ni nanowires with symmetric potential barriers. In these structures, DW propagation was shown to be in the opposite direction to the electron flow as evidenced from current assisted DW depinning measurements. A transition from field dominated DW depinning to SOT dominated DW depinning was observed as the bias current was increased. For SOT dominated DW depinning, the Up-Down DW exhibits a larger depinning field as compared to the Down-Up DW. This is attributed to the interplay between the SOT and Dzyaloshinskii-Moriya interaction in the structure.